(untitled) (Clinics, 2022)
Objective: Stroke is an important cause of disability and death in adults worldwide. However, it is preventable in most cases and treatable as long as patients recognize it and reach capable medical facilities in time. This community-based study investigated students' stroke knowledge, Emergency Medical Services (EMS) activation, associated risk factors, warning signs and symptoms, and prior experience from different educational levels in the KIDS SAVE LIVES BRAZIL project. Methods: The authors conducted the survey with a structured questionnaire in 2019‒2020. Results: Students from the elementary-school (n = 1187, ∼13 y.o., prior experience: 14%, 51% women), high-school (n = 806, ∼17 y.o., prior experience: 13%, 47% women) and University (n = 1961, ∼22 y.o., prior experience: 9%, 66% women) completed the survey. Among the students, the awareness of stroke general knowledge, associated risk factors, and warning signs and symptoms varied between 42%‒66%. When stimulated, less than 52% of the students associated stroke with hypercholesterolemia, smoking, diabetes, and hypertension. When stimulated, 62%‒65% of students recognized arm weakness, facial drooping, and speech difficulty; only fewer identified acute headache (43%). Interestingly, 67% knew the EMS number; 81% wanted to have stroke education at school, and ∼75% wanted it mandatory. Women, higher education, and prior experience were associated with higher scores of knowing risk factors (OR = 1.28, 95% CI: 1.10‒1.48; OR = 2.12, 95% CI: 1.87‒2.40; OR = 1.46, 95% CI: 1.16‒1.83; respectively), and warning signs- symptoms (OR = 2.22, 95% CI: 1.89‒2.60; OR = 3.30, 95% CI: 2.81‒3.87; OR = 2.04, 95% CI: 1.58‒2.63; respectively). Conclusion: Having higher education, prior experience, and being a woman increases stroke-associated risk factors, and warning signs and symptoms identification. Schoolchildren and adolescents should be the main target population for stroke awareness.